2015
DOI: 10.1128/iai.02738-14
|View full text |Cite
|
Sign up to set email alerts
|

The Sensor Histidine Kinase RgfC Affects Group B Streptococcal Virulence Factor Expression Independent of Its Response Regulator RgfA

Abstract: Group B streptococci (GBS; Streptococcus agalactiae) are beta-hemolytic, Gram-positive bacteria that are common asymptomatic colonizers of healthy adults. However, these opportunistic bacteria also cause invasive infections in human newborns and in certain adult populations. To adapt to the various environments encountered during its disease cycle, GBS encodes a number of two-component signaling systems. Previous studies have indicated that the TCS comprising the sensor histidine kinase RgfC and the response r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…RgfA/C regulated the transcription of fbsA and fbsB genes and mediated the binding with the host extracellular matrix fibrinogen, thus participating in the regulation of the adhesion and invasion of GBS to the host cells (Safadi et al., ). Gendrin confirmed that the pathogenicity of rgfC natural deletion mutants was increased, and the ability to infect the brain and spleen tissues of mice increased and the virulence enhanced (Gendrin et al., ). While, in this case, the expression of rgfC of △cel‐EIIB::i strain was significant up‐regulated.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…RgfA/C regulated the transcription of fbsA and fbsB genes and mediated the binding with the host extracellular matrix fibrinogen, thus participating in the regulation of the adhesion and invasion of GBS to the host cells (Safadi et al., ). Gendrin confirmed that the pathogenicity of rgfC natural deletion mutants was increased, and the ability to infect the brain and spleen tissues of mice increased and the virulence enhanced (Gendrin et al., ). While, in this case, the expression of rgfC of △cel‐EIIB::i strain was significant up‐regulated.…”
Section: Discussionmentioning
confidence: 84%
“…The means and standard deviations (mean ± SD) for data were from three independent experiments. Statistical significance of mean values was assessed by a two-tailed Student's t test using SPSS 19.0 software (Gendrin et al, 2015). While, in this case, the expression of rgfC of △cel-EIIB::i strain was significant up-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Because the rgf operon was found to facilitate binding to host cell components and impact virulence in vivo, [ 22 , 23 , 29 ] we sought to better understand the role of the putative autoinducing peptide, RgfD, in phenotypes important for colonization. Similar to prior studies [ 29 , 39 ], we have demonstrated rgf -dependent expression of the rgf operon and have identified genetic variation in the rgf operon genes among a diverse set of GBS strains. The large 881 bp deletion within rgfC is notable given that it was present in almost half of the 40 strains recovered from women with asymptomatic GBS colonization.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations conferring a non-hemolytic, non-invasive phenotype have been detected in the agr operon from strains recovered from patients [ 24 , 28 ]. For the rgf operon, one study identified a truncation in the gene encoding the response regulator, rgfA , in several clinical strains and deletion of both rgfC , the sensor histidine kinase, and rgfA resulted in increased virulence in a mouse and rat model [ 29 ]. This increase was possibly due to other virulence mechanisms including increased sialic acid production and capsule operon transcription, which were both altered in the deletion mutant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation